Molecular mechanism of a potassium channel gating through activation gate-selectivity filter coupling - Wojciech Kopec (Nature Portfolio, 2019)
Potassium channels such as MthK are presumed to have two allosterically coupled gates, the activation gate and the selectivity filter gate, that control gating transitions. Here authors use X-ray crystallography and molecular dynamics simulations on MthK and observe crosstalk between the gates.